Factors associated with occupational injuries among bricklayers and carpenters in Building Construction: insights from a mixed methods study in Osun State, Nigeria - Temitope Olumuyiwa Ojo; Adedeji Ayodeji Onayade; Nisha Naicker (BMC Public Health)
Abstract Background Occupational injuries (OI) remains a global health issue, claiming approximately 1000 lives daily. More needs to be known about OI burdens among artisans in low-income settings. Therefore, this study assessed the factors influencing OIs among carpenters and bricklayers, who are informal artisans in Nigeria. Methods This mixed-methods survey was conducted in Osun state, Nigeria. The quantitative component entailed a comparative cross-sectional study of 421 bricklayers and 425 carpenters selected via simple random sampling. Information on socio-demographics and OI prevalence was obtained using a semi-structured questionnaire. The qualitative aspect comprised 12 focus group discussions (FGD) among artisans who did not participate in the quantitative aspect of the study. Thematic analysis of the qualitative data was conducted to identify pertinent themes and subthemes. Binary logistic regression analysis was conducted to assess the factors influencing OIs, p-value less than 0.05 was taken as statistically significant. Results All respondents were male. The mean age was 51.3.7 ± 14.7 years for bricklayers and 50.0 ± 11.5 years for carpenters. The 3-month prevalence of OI was 39.9% for bricklayers and 51.8% for carpenters. Factors associated with OI among bricklayers included being aged 20–39 years (AOR:6.9, 95% CI:3.1–15.3) and 40–59 years (AOR:2.9, 95% CI:1.5–5.6), earning less than N50,000 (US$67) monthly (OR:2.3, 95% CI:1.2–4.7), earning N50,000-N99,000 (US$67-US$133) monthly (AOR:2.5, 95% CI: 1.2–5.2), and handling ≥ 200 kg per day at work (AOR:2.1, 95% CI:1.3–3.5). For carpenters, factors associated with OI were being aged 20–39 years (AOR:4.1, 95% CI:2.0-8.5), age 40–59 years (AOR:2.1, 95% CI:1.2–3.6) and handling 100–199 kg per day at work (AOR:1.9, 95% CI:1.02–3.4). FGD findings revealed that the use of substandard building materials, poor use of personal protective equipment and working at heights may predispose to OIs. Conclusion The burden of OI is high among informal construction artisans in Nigeria. Safety interventions should target persons < 60 years, those handling heavy weights at work (> 100 kg) and bricklayers earning < N100,000 (< US$134) monthly. Emphasis should also be placed on the use of safety equipment and ensuring standards of building materials.